2022
DOI: 10.1038/s41598-022-07542-4
|View full text |Cite
|
Sign up to set email alerts
|

Grit increases strongly in early childhood and is related to parental background

Abstract: Grit has been identified as a very important non-cognitive skill that is positively related to educational achievements and labor market success. Recently, it has also been found to be malleable through interventions in primary schools. Yet, little is still known about its development in early childhood and the influence of family background. We present an experiment with 429 children, aged 3–6 years. We measure the level of grit as children’s perseverance in a real effort task and their willingness to challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 25 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…The main focus of the current study was to investigate the emergence and development of procrastination in preschool. All age groups were rated as having at least some tendency to procrastinate, replicating Sutter and colleagues’ (2018) initial findings that 3- to 6-year-olds showed evidence of procrastination behavior. Unlike Sutter and colleagues (2018) who reported that younger children procrastinated at higher rates compared to older children, we found that the tendency to procrastinate was rated as more characteristic of older than younger children.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…The main focus of the current study was to investigate the emergence and development of procrastination in preschool. All age groups were rated as having at least some tendency to procrastinate, replicating Sutter and colleagues’ (2018) initial findings that 3- to 6-year-olds showed evidence of procrastination behavior. Unlike Sutter and colleagues (2018) who reported that younger children procrastinated at higher rates compared to older children, we found that the tendency to procrastinate was rated as more characteristic of older than younger children.…”
Section: Discussionsupporting
confidence: 68%
“…To our knowledge, only one study has investigated preschool-aged children’s procrastination behavior. Sutter and colleagues (2018) offered 241 three- to 6-year-old children a choice between completing a bead-sorting task today or postponing the task until tomorrow. Sutter and colleagues (2018) did not report an a priori power analysis but a post hoc power analysis using G∗Power 3.1 (Faul et al, 2007) suggested that they had sufficient power to detect medium- to large-sized effects ( d = .5).…”
Section: Procrastination Versus Task Avoidancementioning
confidence: 99%
See 3 more Smart Citations